Budd-Chiari Syndrome Demonstrated on PET/CT. (August 2017) - Abadie, Brianna; Singh, Manu; Lu, Samson; Daughters, Kenneth
Abstract : Abstract: Budd-Chiari syndrome is a rare clinical condition that involves diminution or interruption of hepatic venous blood flow from the liver. We describe a case of Budd-Chiari syndrome visualized via 18 F-FDG PET/CT in a 60-year-old woman with medical history of B-cell non-Hodgkin lymphoma who presented with abdominal pain. FDG PET/CT fusion images demonstrate increased FDG uptake with SUVmax of 2.2 along the course of the middle hepatic vein with decreased attenuation within both the middle and right hepatic veins, consistent with thrombus.